Secularism and hermeneutics - Almog, Yael (Intellectual history of the modern age., 2019)
Yael Almog examines the works of thinkers such as Johann Gottfried Herder, Moses Mendelssohn, and Friedrich Daniel Ernst Schleiermacher and reveals the tension between textual exegesis and confessional belonging. Secularism and Hermeneutics challenges the modern presumption that interpretation is indifferent to religious concerns.